2019
DOI: 10.3390/cancers11030284
|View full text |Cite
|
Sign up to set email alerts
|

Gliosarcoma Is Driven by Alterations in PI3K/Akt, RAS/MAPK Pathways and Characterized by Collagen Gene Expression Signature

Abstract: Gliosarcoma is a very rare brain tumor reported to be a variant of glioblastoma (GBM), IDH-wildtype. While differences in molecular and histological features between gliosarcoma and GBM were reported, detailed information on the genetic background of this tumor is lacking. We intend to fill in this knowledge gap by the complex analysis of somatic mutations, indels, copy number variations, translocations and gene expression patterns in gliosarcomas. Using next generation sequencing, we determined somatic mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
(81 reference statements)
2
19
0
Order By: Relevance
“…The PI3K pathway is often activated by the silence or genetic loss of phosphatase and tensin homolog and/or the overexpression of protein kinase B [22,23]. The PI3K pathway plays a vital role in carcinogenesis, drug resistance, and programmed cell death of melanoma cells [24][25][26][27][28][29]. Therefore, this pathway is a promising target for melanoma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K pathway is often activated by the silence or genetic loss of phosphatase and tensin homolog and/or the overexpression of protein kinase B [22,23]. The PI3K pathway plays a vital role in carcinogenesis, drug resistance, and programmed cell death of melanoma cells [24][25][26][27][28][29]. Therefore, this pathway is a promising target for melanoma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…GS is generally wild-type - lacks mutations in the genes IDH1/2 [ 3 , 5 , 6 , 7 ]. They have some genetic alterations similar to glioblastomas, such as Phosphatase and tensin homolog (PTEN and PIK3) mutations [7] .…”
Section: Discussionmentioning
confidence: 99%
“…GS is generally wild-type - lacks mutations in the genes IDH1/2 [ 3 , 5 , 6 , 7 ]. They have some genetic alterations similar to glioblastomas, such as Phosphatase and tensin homolog (PTEN and PIK3) mutations [7] . However, collagen gene signature ( COL1A1, COL1A2, COL3A1, COL6A@ , and COL6A3 ) are the gliosarcomas' main biomarkers, differentiating them from glioblastomas [7] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the PI3K/AKT pathway regulates tumor cell survival, growth, motility, angiogenesis, and metabolism in a variety of cancers, including GBM [ 25 , 26 ]. Inhibition of the PI3K/AKT pathway may result in GBM cell death and slow tumor progression [ 27 , 28 ]. It is reported that KIF3C was related to the PI3K/AKT pathway, which lacked a confirmatory experiment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%